Gastrocnemius Medialis and Vastus Lateralis in vivo muscle-tendon behavior during running at increasing speeds - Monte, A.; Baltzopoulos, V.; Maganaris, C. N.; Zamparo, P. (Scandinavian Journal of Medicine & Science in Sports, 2020)
This study combines in vivo ultrasound measurements of the Vastus Lateralis (VL) and Gastrocnemius Medialis (GM) muscles with electromyographic, kinematic, and kinetic measurements during treadmill running at different speeds (10, 13, and 16 km/h) to better understand the role of muscle and tendon behavior in two functionally different muscle-tendon units. In addition, the force-length and force-velocity relationships of VL and GM were experimentally assessed by combining dynamometry and EMG data with ultrasound measurements. With increasing running speed, the operating length of the fascicles in the stance phase shifted toward smaller lengths in the GM (P < .05; moving down the ascending limb of the F-L relationship) and longer lengths in the VL (P < .05; moving down the descending limb) at all speeds; however, both muscles contracted close to their optimal length L0, where isometric force is maximal. Whereas the length of VL SEE did not change as a function of speed, GM SEE lengthened and shortened more at higher speeds. With increasing running speed, the contribution of elastic strain energy to the positive power generated by the MTU increased more for GM (from 0.75 to 1.56 W/kg) than for VL (from 0.62 to 1.02 W/kg). Notwithstanding these differences, these results indicate that, at increasing running speeds, both the VL and GM muscles produce high forces at low contraction velocities, and that the primary function of both muscle-tendon units is to enhance the storage and recovery of elastic strain energy.